Limitations of high pressure sputtering for amorphous silicon deposition. (7th March 2016) - García-Hernansanz, R; García-Hemme, E; Montero, D; Olea, J; Andrés, E San; del Prado, A; Ferrer, F J; Mártil, I; González-Díaz, G
Abstract: Amorphous silicon thin films were deposited using the high pressure sputtering (HPS) technique to study the influence of deposition parameters on film composition, presence of impurities, atomic bonding characteristics and optical properties. An optical emission spectroscopy (OES) system has been used to identify the different species present in the plasma in order to obtain appropriate conditions to deposit high purity films. Composition measurements in agreement with the OES information showed impurities which critically depend on the deposition rate and on the gas pressure. We prove that films deposited at the highest RF power and 3.4 × 10 −2 mbar, exhibit properties as good as the ones of the films deposited by other more standard techniques.